Evaluation of calcification detectability in female breasts by ultra sound - L. FILIPCZYŃSKI; T. KUJAWSKA; G. ŁYPACEWICZ (Archives of Acoustics, 2014)
The authors investigated detectability of calcifications by means of shadow and echo methods for 5 MHz frequency. Computing the ultrasonic field distribution around a rigid sphere they determined the shadow range and hence the detectability condition for calcification diameter Φ ≥ 3 mm. For the echo method former investigations were continued improving the measurement technique and expanding the analysis. To determine the tissue signal background level measurements were performed on 82 breasts of healthy premenopause women. The boundaries of various tissues and inhomogeneities within cause interfering background and its level limits the detectability. The measurement results, confirmed statistically, were used for detectability determination in normal bresst tissues (attenuation 1.1 dB/cm · MHz). The calculations show that the minimum diameter of a detectable calcification Φ = 0.4 mm for a normal breast. JACKSON et al. [18] and KASUMI [19,20] have demonstrated calcifications 0.1-0.5 mm in dia with frequencies of 4 and 7.5 MHz. These results are in general agreement with our theory if one takes into account the high (SD = 8 dB) scattering of the signal background measurement results. When detecting calcifications in the tumor anechoic area one obtains stressing of fine calcification echoes, thus increasing the detect ability when comparing with the case of healthy breast tissues.